Application Of Restorative Justice Towards Perpetrators Aggregated Theft Criminal Act At The East Oku District Prosecutor's Office (Determination Study No. R-1/L.6.21/Eoh.2/03/2025) - Ledina Maharani; Erlina B (International Journal of Education, Vocational and Social Science, 2025)
This research is motivated by the need for alternative approaches in resolving minor criminal cases involving perpetrators of aggravated theft, considering restorative justice as a means of achieving social recovery and participatory justice. The research method used is a qualitative approach with a case study type, employing data collection techniques such as interviews, documentation, and literature study. The results show that the implementation of restorative justice for perpetrators of aggravated theft at the District Attorney's Office of OKU Timur, based on Determination No. R-1/L.6.21/Eoh.2/03/2025, provides an effective and humane solution to resolve minor criminal cases by prioritizing the principles of restorative justice. This process successfully facilitated reconciliation between the perpetrator and the victim, met the victim's needs, fostered the perpetrator's sense of responsibility, and restored social relationships within the community. The inhibiting factors in implementing restorative justice include legal constraints, victim resistance, the perpetrator's lack of understanding, limited resources, and minimal community support. These obstacles indicate the need to strengthen the institutional capacity of the prosecutor's office, expand public legal education, and build more effective collaboration with other law enforcement agencies.